Effect of testosterone in young ice-hockey players on hematological, biochemical parameters and the level of physical performance - N. V. Aksenova; T. A. Mangushev; P. L. Okorokov; E. V. Babaeva; I. V. Zyabkin (National Electronic Information Consortium (NEICON), 2023)
Ice-hockey combines intense physical activity at high speed with elements of power struggle. Testosterone is the main anabolic hormone, an increase in which during adolescence is associated with faster growth, increased muscle mass, physical strength, and increased overall and aerobic performance. Thus, it is interesting to study the effect of different testosterone levels on metabolic parameters and physical performance of young ice-hockey players.Objective: to compare hematological and biochemical parameters, as well as exercise performance in young ice-hockey players, depending on the testosterone level.Materials and methods: the study included 100 young ice-hockey players aged 15-17 years (average age 15.3 ± 1.1 years). The study group included 25 young ice-hockey players with an increased level of total blood testosterone (> 27.5 nmol/l). The control group included 75 young athletes with normal testosterone levels. All athletes included in the study underwent the PWC 170 test to assess physical performance. Assessment of hematological parameters included hemoglobin (HGB), hematocrit, red blood cell, mean corpuscular volume (MCV), mean concentration hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC). β-crosslaps, myoglobin and creatine phosphokinase (CPK) activity were measured to assess the functional state of muscle and bone tissue.Results: A comparative assessment of the CBC in young ice-hockey players did not reveal significant differences depending on the level of serum testosterone level. Tolerance to physical activity in the study groups also did not differ. Young ice-hockey players with increased testosterone levels showed lower β-crosslaps values compared to the control group. The values of other biomarkers of the functional activity of muscle tissue did not depend on the level of testosterone levels.Conclusion: Increased serum testosterone level in the range from 27.5 to 40 nmol/l, detected in young ice-hockey players aged 15-17 years, is not associated with a change in hematological and biochemical parameters. High total testosterone levels do not improve physical performance. It is necessary to continue studies to assess the dynamics of the serum testosterone in young ice-hockey players to clarify the long-term effects of androgens on the metabolic and functional indicators of young athletes. Increasing serum testosterone levels in athletes is subject to wide discussion in the community of sports physicians and endocrinologists.